Proceedings of the 35th International ACM SIGIR Conference on Research and Development in Information Retrieval 2012
DOI: 10.1145/2348283.2348343
|View full text |Cite
|
Sign up to set email alerts
|

Task complexity, vertical display and user interaction in aggregated search

Abstract: Aggregated search is the task of blending results from specialized search services or verticals into the Web search results. While many studies have focused on aggregated search techniques, few studies have tried to better understand how users interact with aggregated search results. This study investigates how task complexity and vertical display (the blending of vertical results into the web results) affect the use of vertical content. Twenty-nine subjects completed six search tasks of varying levels of task… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 32 publications
2
16
0
Order By: Relevance
“…This hypothesis is also supported by the fact that the best performing verticals at higher threshold values are the image oriented verticals (Google Images and Worksheets). The bias towards visual oriented verticals has also been reported before in the literature [4,20]. Anecdotally we also observed that children oriented educational websites (e.g.…”
Section: Distribution Of Relevant Verticalssupporting
confidence: 88%
“…This hypothesis is also supported by the fact that the best performing verticals at higher threshold values are the image oriented verticals (Google Images and Worksheets). The bias towards visual oriented verticals has also been reported before in the literature [4,20]. Anecdotally we also observed that children oriented educational websites (e.g.…”
Section: Distribution Of Relevant Verticalssupporting
confidence: 88%
“…Some studies have explored how search formulation and source selection vary by the level (complexity) of cognitive learning processes based on Bloom's taxonomy [34][35][36]. There are also studies that categorize search tasks using characteristics that can be reduced at least to a certain extent to Bloom's taxonomy.…”
Section: From Learning To Searchingmentioning
confidence: 99%
“…Similarly, Bell and Ruthven defined task complexity as a function of the a priori determinability of the required information, the search strategy, and the ability to judge relevance [9]. Finally, Jansen et al [31] (and later Arguello et al [5] and Wu et al [53]) defined task complexity in terms of the amount of cognitive effort and learning required to complete the task. To this end, they adopted a taxonomy of learning outcomes originally proposed by Anderson and Krathwohl [3] for characterizing educational materials.…”
Section: Task Complexitymentioning
confidence: 99%